Comparative overview of basic cybervulnerabilities of mobile applications for Android operating system - Dubrovskyi, M. S.; Semenov, S. G. (Харківський університет Повітряних Сил ім. Івана Кожедуба, 2016)
With the market for mobile applications for Android platform constantly growing and more security-dependent tasks moving to mobile platforms, security of Android applications is a major concern for developers and users. In this paper, an overview of Android operating system security model is given. Components of Android application are studied, with special attention given to mechanisms of Inter-process communication via Intents. An overview of basic vulnerabilities of Android applications and vulnerabilities of IPC in Android applications is performed.

Враховуючи постійне зростання ринку мобільних застосувань для платформи Android, а також переміщення завдань, що вимагають підвищеної безпеки, на мобільні платформи, безпека додатків Android стає пріоритетом для розробників і користувачів. У даній статті проводиться аналіз моделі безпеки операційної системи Android, розглядаються компоненти додатків Android, особливо механізми взаємодії між процесами (IPC) за допомогою об'єктів Intent, проводиться огляд основних уразливостей додатків Android і уразливостей взаємодії між процесами, пропонуються механізми обходу уразливостей.
Порівняльний огляд основних кіберуразливостей мобільних застосувань для операційної платформи Android
Keywords: security; inter-process communication; vulnerability; attack vectors; безпека; уразливість; вектор атаки